Control of haemonchosis in Malaysian goats with closantel - Dorny, Pierre; Vercruysse, Jozef; Abu, Jalila; Abdullah Sani, Rehana; Symoens, Chantal (Elsevier Science, 1994)
The therapeutic and prophylactic effects of closantel on natural infections with Haemonchus contortus were studied in goats in Peninsular Malaysia. Closantel was highly effective against H. contortus, either at a subcutaneous (s.c.) injection of 5.0 mg kg- ~ body weight (100%), or in an oral drench mixture with mebendazole at a dose of 10.0 mg kg-(99.2%), as indicated by faecal egg counts. H. contortus larvae were absent from faecal cultures for 5, 6 and 7 weeks following treatment with s.c. injections of closantel at doses of 2.5 mg kg- 1, 5.0 mg kg- ~ and 10.0 mg kg- 1 respectively, and for 6 weeks after treatment with closantel at 10.0 mg kg -1, given orally. Through its sustained activity, closantel not only prevented reinfection with H. contortus but also caused a dramatic reduction in pasture contamination. The potential utility of closantel in the strategic control of haemonchosis in goats, and as an alternative treatment for benzimidazoles and levamisole resistant H. contortus strains, is discussed.